2012
DOI: 10.1097/wnp.0b013e3182570eff
|View full text |Cite
|
Sign up to set email alerts
|

The Second Lumbrical–Interosseous Latency Comparison in Carpal Tunnel Syndrome

Abstract: Carpal tunnel syndrome (CTS) is the most common nerve entrapment syndrome. Electromyogram (EMG) is beneficial in supporting the diagnosis of CTS. We compared standard nerve conduction studies of EMG with median and ulnar motor nerve conduction studies from recordings of second lumbrical and interosseal muscles in supporting the diagnosis of CTS. In this study, a total of 242 patients were included, and a total of 375 hands were involved. Electrophysiologic CTSs were diagnosed in 283 hands of 161 patients. A si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 17 publications
0
12
1
Order By: Relevance
“…Furthermore, Ozben et al [26] found the sensitivity to be 89.4% and specificity to be 84.4% with a cut-off value of ≥0.5 in their study. However, based on a cutoff value of >0.5 for L-I latency difference, sensitivity and specificity were 86.9% and 91.3%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Ozben et al [26] found the sensitivity to be 89.4% and specificity to be 84.4% with a cut-off value of ≥0.5 in their study. However, based on a cutoff value of >0.5 for L-I latency difference, sensitivity and specificity were 86.9% and 91.3%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, clinicians perform a second lumbrical-interosseous latency comparison (2 L-INT) test (Kaul and Pagel 2002;Nobuta et al 2005;Sheean et al 1995). However, in the absence of 2 L-CMAPs (Inukai et al 2013;Ozben et al 2012), it is very difficult to quantitatively evaluate CTS severity using NCS. Some authors report that ulnar nerve distal motor latency (DML) and distal sensory latency can be significantly longer in patients with CTS than in controls (Chen and Tsai 2014;Kiylioglu et al 2011;Yemisci et al 2011).…”
Section: Introductionmentioning
confidence: 97%
“…Neurophysiological data was collected based on the extensive and complete description of previous study designs by Padua [4] and Bland [6] and which is understood to be followed by most of the clinical laboratories in the United Kingdom. In addition, Second Lumbrical-Interosseous Latency was also recorded to distinguish between ‘very severe’ and ‘complete absent’ response grading of CTS [10].…”
Section: Methodsmentioning
confidence: 99%
“…Amplitude was recorded from peak to peak for sensory responses, and base to peak for motor responses. If responses were not recordable from median sensory digit II, III and motor from APB muscles, then motor responses were elicited by placing recording electrodes on 2nd lumbricals by stimulating median and ulnar nerves at the wrist [7, 1012].…”
Section: Methodsmentioning
confidence: 99%